그린촉매를 이용한 산화반응 : 에스터, 싸이오에스터, 아마이드, 싸이오아마이드의 합성 - 지미란 (The Graduate School, Ajou University, 2015)
The thioamides functional group has been commonly found its application in biochemistry like antithyroid drugs. It is also used in industrial application as vulcanization agents and grease additives. Previous reported methods for the synthesis of thioamides involved the use of excess amount of sulfur transfer agent which is desirable from the environmental point of view. Herein, we proposed a method for the synthesis of thioamides using a copper catalyzed aerobic oxidation of thiols. This protocol seems to be more step-economic and atomeconomic as it avoids the use of exogenous sulfur reagent.
학위논문(석사)--아주대학교 일반대학원 :에너지시스템학과,2015. 2
Keywords: 촉매